Seismic Response of a Tunnel Embedded in Compacted Clay through Large-Scale Shake Table Testing - Hao Zhou; Xinghua Wang; Changdi He; Changxi Huang (Shock and Vibration)
To investigate the seismic response of large-scale tunnel in compacted clay and effect of shock absorbing layer to the tunnel, a series of three dimensional (3D) shaking table model tests were carried out. The similarity ratio of the model is 1 : 8 and the size of the model container is 9.3 m (length) × 3.7 m (width) × 2.5 m (height). The cross-sectional diameter of the model tunnel is 0.9 m, and the thickness of the tunnel lining is 0.06 m. To simulate the clay soil surrounding condition, the container was filled with clay soil. During the tests, the concrete strain, acceleration, and dynamic soil pressure on the surface of the model tunnel were measured. The results show the existence of tunnel can decrease the maximum acceleration of the model in the X direction; the shock absorbing layer can further decrease the maximum acceleration, however, cannot change the dominant frequency of the ground motion. The longitudinal and hoop strain of the model tunnel with excitation of the input motion is mainly in tension state and the maximum hoop deformation of the model tunnel is located at the conjugate 45°. In addition, the shock absorbing layer has an effect on the strain and dynamic earth pressure of the model tunnel.